Promotores As Advocates for Community Improvement: Experiences of the Western States REACH Su Comunidad Consortium. Issue 4 (October 2015) - Kutcher, Rachel; Moore-Monroy, Martha; Bello, Elizur; Doyle, Seth; Ibarra, Jorge; Kunz, Susan; Munoz, Rocio; Patton-Lopez, Megan; Sharkey, Joseph R.; Wilger, Susan; Alfero, Charlie
Abstract : The REACH Su Comunidad Consortium worked with 10 communities to address disparities in access to healthy food and physical activity opportunities among Hispanic populations through policy, systems, and environmental (PSE) strategies. Community health workers took leadership roles in the implementation of PSE strategies in partnership with local multisector coalitions. This article describes the role of community health workers in PSE change, the technical and professional development support provided to the REACH Su Comunidad Communities, and highlights professional development needs of community health workers engaging in PSE strategies.